Proteomic profiling of yellow catfish (Pelteobagrus fulvidraco) skin mucus identifies differentially-expressed proteins in response to Edwardsiella ictaluri infection. Issue 100 (May 2020) - Xiong, Yang; Dan, Cheng; Ren, Fan; Su, ZiHao; Zhang, Yibing; Mei, Jie
Abstract: Fish mucus acts as a physiological and immunological barrier for maintaining normal fish physiology and conferring defense against pathogens infection. Here we report proteomic profiling of skin mucus of yellow catfish before and after E. ictaluri infection by Label-free LC-MS/MS approach. A total of 918 non-redundant proteins were identified from 54443 spectra referring to yellow catfish genome database. Further annotation via GO and KEGG database revealed complex protein composition of yellow catfish mucus. Besides structural proteins in mucus, a lot of immune-related proteins were retrieved, such as lectins, complement components, antibacterial peptides and immunoglobins. 133 differentially-expressed proteins (DEPs), including 76 up-regulated and 57 down-regulated proteins, were identified, most of which were enriched into 17 pathways centering on "immune system" category with 33 proteins involved. Consistently, significant proliferation of mucus-secreting goblet cells and CYPA-expressing cells were observed along outside of yellow catfish skin after E. ictaluri infection, indicating an enhanced immune response to E. ictaluri infection in yellow catfish skin mucus. The proteomic data provide systematic protein information to comprehensively understand the biological function of yellow catfish skin mucus in response to bacterial infection. Highlights: Proteome profiling reveals composition of yellow catfish skin mucos before and after E. ictaluri infection. 133 differentially expressed proteins (DEPs) were identified and a highest proportion of DEPs are immune-related proteins. Increased proliferation of secretory cells was observed in mucus after E.ictaluri infection.